KONSEP INFORMATIKA DAN COMPUTATIONAL THINKING DI DALAM KURIKULUM SEKOLAH DASAR, MENENGAH, DAN ATAS - Ayu Pertiwi; Abdul Syukur; Titien Suhartini; Affandy Affandy (LPPM UNIVERSITAS DIAN NUSWANTORO, 2020)
Informatics or computer science is an important subject for school education today. Informatics can be presented as a scientific discipline to understand technology in a way that is more deeply behind computer programs. With the introduction of informatics to schools is to prepare young people to become creators of information technology not just users of information technology. To achieve this, informatics concepts need to be introduced from basic education, high school, and high school. On the other hand, we need to help people solve problems by using technology and developing computational thinking in various fields. This paper presents the role of Indonesia specifically through universities in Indonesia in introducing computational thinking through Bebras Computational Thinking.